2018
DOI: 10.1002/jocb.373
|View full text |Cite
|
Sign up to set email alerts
|

Change it Up: Inactivity and Repetitive Activity Reduce Creative Thinking

Abstract: Across three experiments, we show that a change in the levels of physical activity increases creative thinking, whereas inactivity or repetitive activity lowers it. Participants walking forward were more creative the first few minutes of initiating physical activity than those sitting, or those merely watching changing scenery, and these effects dissipated when they continued the forward movement over time (within 8 minutes). Furthermore, merely anticipating a change in physical activity, for example, when par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
1
2
0
1
Order By: Relevance
“…The findings of the present meta-analyses are in line with the general assumption that physical activity offers a change, that is the transition from one state to the other, which could enhance the quality and the quantity of ideas by preparing people to deal with these changes [ 96 , 98 ]. Main et al [ 98 ] showed in three experiments that changes in physical activity enhanced creative thinking, while inactivity or repetitive physical activity lowered it. However, this line of argumentation is strongly restricted to acute effects of physical activity and does not provide explanations for the stronger chronic effects of physical activity on creative ideation performance.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The findings of the present meta-analyses are in line with the general assumption that physical activity offers a change, that is the transition from one state to the other, which could enhance the quality and the quantity of ideas by preparing people to deal with these changes [ 96 , 98 ]. Main et al [ 98 ] showed in three experiments that changes in physical activity enhanced creative thinking, while inactivity or repetitive physical activity lowered it. However, this line of argumentation is strongly restricted to acute effects of physical activity and does not provide explanations for the stronger chronic effects of physical activity on creative ideation performance.…”
Section: Discussionsupporting
confidence: 83%
“…Based on the broaden and build theory, which assumes that positive affect coincides with more original ideas via cognitive flexibility [ 65 , 124 ], the physical activity-associated affective shift was suggested to increase creative ideation performance [ 43 , 87 , 125 ]. Although this hypothesis has been investigated with cross-sectional and intervention studies, to the best of our knowledge, no study to date has confirmed the implied mediating role of positive affect on creative ideation outcome [ 43 , 82 , 98 , 108 ]. However, as outlined by Biddle et al [ 6 ], the effects of physical activity on stress (negative affect) and positive affect in ecologically valid settings could be a fruitful area for future research [ 43 , 126 ].…”
Section: Discussionmentioning
confidence: 99%
“…As Zheng (2013) observed, to get higher scores in the highly competitive entrance examination of high school and college, those Chinese students chose to practice a lot of repetitive exercises. The results of some behavior experiments suggested that repetitive activity could reduce the diverse thinking of subjects' (e.g., Main et al, 2020). Furthermore, the repetitive exercises would lead to fast habituation (can be observed by skin conductance records) which hurts the creative thinking of participants (Martindale et al, 1996).…”
Section: Possible Reasons Of the Grade Effect Of The Score Of The Hom...mentioning
confidence: 99%
“…Flórez et al (2018) La metacognición Proponen la metacognición como una estrategia, permitiendo al sujeto controlar lo que aprende de manera significativa. Main et al (2020) Danza aeróbica Proponen como estrategia la danza aeróbica para desarrollar el pensamiento creativo. Las personas que realizan ejercicio aeróbico muestran un pensamiento más divergente que aquellas que no lo hacen.…”
Section: Montaño (2020)unclassified